Insights into Math Word Problems: Developing Learning Cycle for solving Word Problems - KAPOOR, ARUSHI (THE PRIMARY TEACHER, 2016)
Word problems in mathematics are real-time problem situations, which can be solved using mathematical concepts. Inclusion of word problems in school mathematics curriculum aims to inculcate problem-solving skills among children. Word problems have always caught the attention of researchers because children face many learning challenges while working on word problems. This paper discusses the outcome of an empirical study conducted on fourth and fifth grade students to find out the learning difficulties they face and learning patterns they follow while working on word problems. George Polya’s classical work (1945) on problem-solving and Anne Newman’s seminal work (1977) on the working of word problems were used to develop conceptual framework for the study. An in-depth analysis was done to develop insights into the processes adopted by students at various levels of solving word problems. Findings of the study were used to construct suggestive learning framework for solving word problems.